THE VALIDITY OF STUDENT WORKSHEET BASED PROJECT IN TRAINING STUDENTS’ CRITICAL THINKING FOR 8th MTs ON EXCRETION SYSTEM MATERIALS (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
The purpose of this study is to develop project based learning worksheets on excretion system material for class VIII MTs based on validity test. In project based learning, excretory system material is material connected to life. This is a form of development research with reference to the ADDIE development model, which has 5 stages: (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. However, the Implementation did not take place in this research. The acquired data was descriptively examined quantitatively and qualitatively. The outcomes of the LKPD development are consistent with the revisions of the supervising lecturers and validators consisting of media expert lecturers, subject matter expert lecturers, and science teachers. Based on the outcomes of the development assessment of project based learning worksheet obtained an average validation result from the validator of 3,68 with a very valid category. So, it can be conclude that the development of project based learning worksheets on excretion system material for class VIII MTs. which developed with the ADDIE development model is very valid for use in learning.